Population analysis in aspect of specifying suitable property area using data driven documents (D3) data visualization technique / Mohd Asyraf Md Surani - Md Surani, Mohd Asyraf (2018)
In the era of globalization, data information are increasing day by day where more daily data continue to increase across the globe. Data is important and can be confidential to certain industries or organizations that can make the data meaningful. Data of population nowadays become a trend of analysis that can make some prediction on development based on the population data. Problem statements defined in this project are the data information on population are left unstructured and disorganized due to lack information. As consequences to this problem, it can be hard to analyse the unpredicted data of the population area. This project aims to perform population analysis in aspect of specifying suitable property area with Data Driven Documents (D3) data visualization method. The objectives of this project are to analyse data with visualization using D3 tool and make prediction on the population for the year 2020 in Perak state. D3 technique is a technique to visualize the data interactively and dynamically. The methodology of this project involves planning, design, analysis, testing and maintenance. The data of population are collected and organized manually from the Department of Statistics Malaysia (DOSM) page that are stored into the database which is CSV file. This extracted data is being implemented on the parallel coordinate graph to display the data to make it more user-interactive. Analysis phase defines a suitable method to analyse about the data population. Exponential model equation method are suitable in making the prediction of the future population of Perak state in year 2020. The prediction data are implemented and displayed on D3 interactive map to provide the meaningful information for user. The case study about Perak state has been done by defining the number of districts in Perak and the year of prediction is 10 years from the available collected data. In conclusion, the benefit of this project is to ease the user to gain useful information about the population in Perak state by having an early planning for the future development.